2001
DOI: 10.1001/archotol.127.4.412
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Assisted Uvulopalatoplasty for Snoring

Abstract: The favorable subjective short-term results of laser-assisted uvulopalatoplasty deteriorated with time. In addition, postoperative nocturnal polysomnography showed that the procedure caused mild obstructive sleep apnea in a considerable number of patients who formerly were nonapneic snorers. These findings may be related to velopharyngeal narrowing and progressive palatal fibrosis, caused by the thermal damage inflicted by the laser beam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Although the short-term success rates are high, these rates decrease in the long-term. Berger et al [17] , in their 24-month fol- low-up, found a short-term success rate of 79% but in the long-term follow-up, the rate declined to 57%. Osman et al [4] found a success rate of 82.8% in the postoperative period and this rate declined to 75.9% in the long-term.…”
Section: Discussionmentioning
confidence: 94%
“…Although the short-term success rates are high, these rates decrease in the long-term. Berger et al [17] , in their 24-month fol- low-up, found a short-term success rate of 79% but in the long-term follow-up, the rate declined to 57%. Osman et al [4] found a success rate of 82.8% in the postoperative period and this rate declined to 75.9% in the long-term.…”
Section: Discussionmentioning
confidence: 94%
“…[53][54][55] Few studies, however, have analyzed outcome assessment beyond 2 years postoperatively. [53][54][55] Few studies, however, have analyzed outcome assessment beyond 2 years postoperatively.…”
Section: Vascular Lesionsmentioning
confidence: 99%